Isolation and Characterization of a Novel Alphaherpesvirus in Fruit Bats - Sasaki, Michihito (American Society for Microbiology, 2014)
Bats are known to harbor emerging RNA viruses. Recent studies have used high-throughput sequencing technology to identify various virus species, including DNA viruses that are harbored by bats; however, little is known about the nature of these potentially novel viruses. Here, we report the characterization of a novel herpesvirus isolated from an Indonesian pteropodid bat. The virus, tentatively named fruit bat alphaherpesvirus 1 (FBAHV1), has a double-stranded DNA genome of 149,459 bp. The phylogenetic analyses suggested that FBAHV1 is phylogenetically grouped with simplexviruses within the subfamily Alphaherpesvirinae. Inoculation of FBAHV1 into laboratory mice caused a lethal infection. Virus infection was observed in lung, liver, and brain tissue. Serological and PCR screening revealed that fruit bats infected with FBAHV1 or its related virus are widely distributed in Indonesia. The identification of FBAHV1 makes a considerable contribution to our understanding of simplexviruses associated with bats. IMPORTANCE Bats are known to harbor emerging viruses, such as lyssaviruses, henipaviruses, severe acute respiratory syndrome-like coronaviruses, and filoviruses. Although alphaherpesviruses are disseminated in humans and other animals, there is little information about their distribution in bats. Here, we isolated a previously unknown alphaherpesvirus from an Indonesian fruit bat. Genome sequence analysis suggested that the virus is a member of the genus Simplexvirus within the subfamily Alphaherpesvirinae, which also includes common human viruses, such as herpes simplex virus 1 and herpes simplex virus 2. FBAHV1 is the first bat-derived alphaherpesvirus whose complete genome has been sequenced.